OVARIAN FACTOR ENDOCRINO - Morán, Carlos (2015)
In reproductive endocrinology, the endocrine ovarian factor is known as the hormonal alterations conditioning infertility in women, originating in the ovary or affecting the ovarian function. The ovary is regulated by neuroendocrine mechanisms, with the fundamental participation of the hypothalamus and the pituitary gland, in conjunction with other endocrine glands like thyroid and adrenals, and with an additional regulation from the pancreas and adipose tissue. The main endocrine disorders in women with infertility include: polycystic ovary syndrome, hyperprolactinemia, non classical adrenal hyperplasia, hypothalamic amenorrhea, premature ovarian failure, and thyroid disease. The evaluation of these disorders is based on the particular symptoms mainly affecting the menstrual cycle, and with the determination of diverse hormones. Treatment is focused on the correction of each causal disorder and ovulation induction if possible. With the exception of premature ovarian failure, the prognosis for fertility is favorable for most of these disorders, obtaining approximately 80% of pregnancy rate following two years of treatment.